Nanocellulose/two dimensional nanomaterials composites for advanced supercapacitor electrodes - Liang, Qidi; Wang, Yaxuan; Yang, Yanfan; Xu, Ting; Xu, Ying; Zhao, Qingshuang; Heo, Su-Hak; Kim, Min-Seok; Jeong, Young-Hwan; Yao, Shuangquan; Song, Xueping; Choi, Sun-Eun; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
With the emerging of the problems of environmental pollution and energy crisis, the development of high-efficiency energy storage technology and green renewable energy is imminent. Supercapacitors have drawn great attention in wearable electronics because of their good performance and portability. Electrodes are the key to fabricate high-performance supercapacitors with good electrochemical properties and flexibility. As a biomass based derived material, nanocellulose has potential application prospects in supercapacitor electrode materials due to its biodegradability, high mechanical strength, strong chemical reactivity, and good mechanical flexibility. In this review, the research progress of nanocellulose/two dimensional nanomaterials composites is summarized for supercapacitors in recent years. First, nanocellulose/MXene composites for supercapacitors are reviewed. Then, nanocellulose/graphene composites for supercapacitors are comprehensively elaborated. Finally, we also introduce the current challenges and development potential of nanocellulose/two dimensional nanomaterials composites in supercapacitors.